Behavioural and emotional development in children of divorce - Molepo, Lephodisa Stephen; Sodi, Tholene; Maunganidze, Levison; Mudhovozi, Pilot (National Inquiry Services Centre, 2021)
This study reports on teacher perceptions of the impact of parental divorce on behaviour and emotional development in children of divorce. Participants were a purposive sampling of 80 primary school learners with parental divorce experience and a comparison group of 40 others from typical or intact families (n = 120: males = 64; females = 56; age range = 6 to 12 years). Teachers completed the Conners' Rating Scales—Revised (CRS—R: Conners, 1998; Casat et al., 1999) on each of the learners. The findings suggest that teachers perceive younger children from divorced parents were more likely to have emotional and behavioural challenges than those from intact families. By contrast, teachers perceived older children from intact were to have emotional and behavioural difficulties.